VPNs as boundary objects of the internet: (Mis)trust in the translation(s) - Luke Heemsbergen; Adam Molnar (Internet Policy Review, 2020)
How do we come to trust, use and govern virtual private networks (VPNs)? How do these objects of the internet tack back and forth between metaphor and technical processes as they garner usership and critique? This paper aims to answer these questions by considering VPNs as boundary objects. We follow Susan Leigh Star's (2010) call to further explore the "tacking" back and forth of boundary objects as both symbolic and technical objects. This is applied within internet-space and governance-space through empirical methods that walkthrough a typical user experience for acquiring VPN services, while also offering a systemic account of the discourse that such a user would experience in coming to understand VPNs and their function.
Keywords: 300; Boundary object; Metaphor; Regulation; Privacy; Security